Etnomatematika sebagai salah satu upaya penguatan kearifan lokal dalam pembelajaran matematika - Maria Isabella Chrissanti (Math Didactic: Jurnal Pendidikan Matematika, 2018)
Globalization slowly threaten the nation’s noble values inherited from the ancestors. Local wisdom values which is a part of a nation's identity, is often forgotten as the life becomes more and more modern. If this kind of situation keep happening continously, then this nation might be lost their identity. Hence, strengthening the local wisdom is something that needs to be seriously conducted, with education being one of the means. This study talk about the effort to strengthening the local wisdom in learning process, especially in mathematics learning through culture based learning. In 1985, D’Ambrosio introduce the concept of culture based learning in mathematical context known as ethnomathematics. In general, ethnomathematics can be saw as concepts of mathematics in a cultural and anthropological framework. In ethnomathematics, students were not only encouraged to improve their math skills, but also preserving culture which is the nation's indigenous character. Therefore, ethnomathematics is considered relevant in not only improving the students' math skills, but also strengthens their local wisdom values.